A survey of members of the European Surveillance System on Contact Allergy and the EU project "StanDerm" to identify allergens tested in cosmetic series across Europe. (3rd January 2020) - Horton, Emma; Wilkinson, Mark; Aalto‐Korte, Kristiina; Pesonen, Maria; Bauer, Andrea; Chowdhury, Mahbub M.U.; Cooper, Susan; Cousen, Philippa; Crépy, Marie‐Noëlle; Larese Filon F, Francesca; Gallo, Rosella; Geier, Johannes; et al.
Abstract: Background: There is currently no agreed cosmetic series for use across Europe. Objectives: To establish allergens currently tested in local and national cosmetic series. Method: Members of the European Surveillance System on Contact Allergy and the European Cooperation in Science and Technology project TD1206 ("StanDerm") were surveyed to establish their current practice. Results: A wide range of allergens was tested but there was significant variation between centres on the allergens considered to be important in screening for allergy to cosmetics. The number of allergens tested in addition to the baseline series varied between 2 and 50. Conclusions: There is a need for further investigation to establish the frequency and relevance of reactions to cosmetic allergens to enable an agreed evidence‐based cosmetic series to be produced. Criteria for inclusion need to be established.